Pengembangan Karakter Religius Melalui Kegiatan Kerohanian Islam - Melinda, Ertin; Maksum, Muh. Nur Rochim; Utomo, Agung Wahyu (Universitas Muhammadiyah Yogyakarta, 2022)
teenagers, especially vocational schools, who are experiencing a moral decline. One of its missions is to develop religious character. However, not all students can apply religious values. Therefore, one of the ways is through Islamic spiritual activities (Rohis) which are Islamic organizations in schools to improve the religious character of students. There are also many issues that state that Rohis have become a radical organization and that intolerance has developed in the school environment. The purpose of this research is to find out the forms of Spiritual extracurricular activities that can improve the religious character of students and the results of the role of Spiritual extracurricular activities in improving the religious character of students. The approach used is a qualitative approach. While the data collection techniques used are interviews, observation and documentation. Data analysis used is data reduction, data presentation and conclusion. The results obtained in this study indicate that in the process of character formation through various Islamic spiritual activities including chanting asmaul husna, studies, PHBI, training of trainers and vocal grub sholawatan. It turns out that in spiritual activities this has not been fully realized, for example Habblum Minallah, Hablum Minannas which is more dominant which has been realized and for Hablum Minal'Alam only in certain activities that can be realized. The implication of the research is to increase the religious character of students through Islamic spiritual activities (Rohis) in the form of Islamic forums, teaching and da'wah.